Understanding the emergent attributes of 21st-century mathematics teachers in Bukidnon - Ucang, Jenyliza T.; Limjap, Auxencia A. (Technium Social Sciences Journal, 2021)
Numerous quantitative research studies from abroad and in the Philippines had been investigating the attributes of the mathematics teachers in the 21st - Century. A study using grounded theory was designed to find out the attributes of 21st -century mathematics teachers in Bukidnon. Thirteen participants were interviewed over a period of four months. Interviews were analyzed using Pandit’s grounded theory methodology and the constant comparison method. Three main categories and thirty-nine subcategories have been identified and explained that encompasses an emerging substantive theory of “Understanding the Emergent Attributes of 21st -Century Mathematics Teachers in Bukidnon” which are as follows: 1) Knowledge (community, curriculum, educational foundation and policies, environmental awareness, global awareness, pedagogy, students, subject content, self); 2) Skills (administrative and management skills, communication skills, facilitative skills, pedagogical skills, people management skills, reflective skills and thinking disposition, social and emotional intelligence and technological skills; and 3) Values (accurate, adaptive and resilient, aim for high standards, belief that all children can learn, collaborative learning and practice, commitment to nurturing the potential in each child, creative, empathy, enquiring nature, ethical, objective, passion, prayerful, perseverance, productive, professionalism, resourceful, social responsibility and engagement, stewardship, strive to improve, value parental involvement and valuing diversity). Further, the study revealed that the value of a person influences the teacher on what he will teach and directs the teacher on how he will teach the subject content.